2009
DOI: 10.1002/chem.200902183
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Properties and OLED Applications of Phosphorescent Platinum(II) Schiff Base Complexes

Abstract: The syntheses, crystal structures, and detailed investigations of the photophysical properties of phosphorescent platinum(II) Schiff base complexes are presented. All of these complexes exhibit intense absorption bands with lambda(max) in the range 417-546 nm, which are assigned to states of metal-to-ligand charge-transfer ((1)MLCT) (1)[Pt(5d)-->pi*(Schiff base)] character mixed with (1)[lone pair(phenoxide)-->pi*(imine)] charge-transfer character. The platinum(II) Schiff base complexes are thermally stable, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
197
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(216 citation statements)
references
References 56 publications
8
197
2
1
Order By: Relevance
“…Nonetheless, our devices perform quite well in comparison to sublimed platinum(II) complexes with N^C^N tridentate ligands (h c,max = 15-40 cd A À1 , L max = 3500-12 100 cd m À2 ) [16] or O^N^N^O Schiff base tetradentate units (h c,max = 1.6-31 cd A À1 , L max = 3000-20 000 cd m À2 ). [17] The efficiency of small-molecule OLEDs is higher owing to a more sophisticated device configuration. However, solution-processable emitters would enable a cost-effective fabrication.…”
mentioning
confidence: 99%
“…Nonetheless, our devices perform quite well in comparison to sublimed platinum(II) complexes with N^C^N tridentate ligands (h c,max = 15-40 cd A À1 , L max = 3500-12 100 cd m À2 ) [16] or O^N^N^O Schiff base tetradentate units (h c,max = 1.6-31 cd A À1 , L max = 3000-20 000 cd m À2 ). [17] The efficiency of small-molecule OLEDs is higher owing to a more sophisticated device configuration. However, solution-processable emitters would enable a cost-effective fabrication.…”
mentioning
confidence: 99%
“…[17] Die Effizienz von OLEDs mit kleinen Molekülen ist wegen ihrer anspruchsvollen Struktur höher, doch würden in Lösung prozessierbare Emitter eine kostengünstigere Herstellung ermöglichen.…”
Section: Sublimation Hergestellt Wurden Und Ptunclassified
“…The doping rate of the emissive layer plays a key role in the efficiency and the color emission of devices. It was demonstrated that the device efficiency increased with a concentration of platinum (II) dopant, up to 5 wt % or 6 wt % depending on the platinum(II) complex [16]. By considering a 6 wt % concentration of [Pt] (with Alq3 number density ~10 21 cm −3 [17]) and by assuming that the Ptcomplexes do not aggregate, the number density of Pt-complex is estimated at about 6.10 19 [Pt]/cm 3 and the average distance between neighboring complexes at ~ 3 nm.…”
Section: Host-guest Systemmentioning
confidence: 99%
“…Thereby, the effective distance over which the energy transfers between complexes (estimated at 3 nm) would be higher than the radius of triplet-triplet annihilation (<1 nm through Dexter mechanism) [18][19][20]. Furthermore, the steric hindrance between adjacent molecules induced by the tert-butyl substituents of [Pt] tends to limit the formation of [Pt] aggregates and hence reduces aggregation-induced phosphorescence quenching in thin solid film [15,16]. Consequently, doping rate of [Pt] is fixed at 6 wt % to maximize the performance of the devices.…”
Section: Host-guest Systemmentioning
confidence: 99%
See 1 more Smart Citation